PERURAIAN LIMBAH MAKANAN MENGGUNAKAN BIOREAKTOR AEROBIK DALAM FASA SUSPENSI - Soeprijanto Soeprijanto (Purifikasi, 2009)
The purpose of this study was to degrade food wastes to simple compounds. The experiments were conducted using a slurry aerobic bioreactor with a working volume of 25 L. The bioreactor was aerated with an air flow rate of 12 L/min and an organic loading rate of 2 g/L.day. Parameters determined during operations were total solids, COD, dissolved oxygen, pH, total nitrogen and total phosphorous. The results showed that during operation time of 90 days, the oxygen requirement for degradation of food waste was 0.35 g O2/g dry weight. The degradation of solid waste was 79.60% and the removal efficiency of total COD was 79.40%. Dissolution and mineralization of food wastes achieved maximum nitrogen concentration of 123.3 mg NH4-N/L and that of phosphorus of 32.2 mg PO4-P/L. It concluded that the aerobic bioreactor could decompose fresh food wastes during a time period of 90 days without intermittent removal of suspended solids in the system.